Bioactivity Study of Russelia equisetiformis Ethanol Extract as an MCF-7 Breast Cancer Cells Inhibitor with In vitro and In silico Approaches - Rizq Rachmad Ramiizah; Dini Attala Hefa Insyira; Najwa Salsabila Hakim; Muhammad Rafly Aditya Firmansyah; Tukiran Tukiran (Science and Technology Indonesia, 2026)
Russelia equisetiformis has been used in traditional medicine, but its molecular mechanisms against breast cancer remain unexplored. This study aimed to investigate the cytotoxic potential of R. equisetiformis ethanol extract and elucidate its molecular interactions through a combined in vitro and in silico approach. Cytotoxicity evaluation using the Resazurin assay demonstrated the extract’s activity against MCF-7 breast cancer cells with an IC50 value of 352.60 ± 0.23 ????g/mL. To understand the underlying mechanism, the identified bioactive compounds that passed the druglikeness test were analyzed using molecular docking against the Progesterone Receptor (PDB ID: 2W8Y) and Estrogen Receptor-alpha (PDB ID: 3ERT). Docking analysis revealed that these compounds form binding interactions with target receptors, providing insight into their potential mechanism of action, albeit with lower affinity compared to standard drugs (tamoxifen and anastrozole). Importantly, ADMET prediction using ProTox 3.0 highlighted apigenin, kaempferol, isokaempferide, and kaempferol 3-O-rhamnoside as the most promising primary candidates, demonstrating inactivity against hepatotoxicity, carcinogenicity, and cytotoxicity. These findings provide initial scientific evidence for the potential anticancer properties of R. equisetiformis compounds, indicating that all four compounds are safe and viable bioactive candidates for further development as non-toxic therapeutic agents.